Proceedings. 42nd Design Automation Conference, 2005. 2005
DOI: 10.1109/dac.2005.193876
|View full text |Cite
|
Sign up to set email alerts
|

Traffic shaping for an FPGA based SDRAM controller with complex QoS requirements

Abstract: Today high-end video and multimedia processing applications require huge amounts of memory. For cost reasons, the usage of conventional dynamic RAM (SDRAM) is preferred. However, SDRAM access optimization is a complex task, especially if multistream access with different QoS requirements is involved. In [8], a multi-stream DDR-SDRAM controller IP covering combinations of low latency requirements for processor cache access, hard realtime constraints for periodic video signals and hard real-time bursty accesses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Very recently, shaping has also been used in the particular context of designing multi-processor System-on-Chip (SoC) architectures. It has been shown that shaping on-chip traffic leads to reduced on-chip global buffer requirements and improves overall system performance and predictability [8,14]. Similar techniques have also been shown to be useful when applied to Networks-on-Chip (NoC) architectures, where again they result in improved worstcase response times and global buffer requirements (which in turn lead to reduced chip area and power consumption) [10].…”
Section: Relation To Previous Workmentioning
confidence: 95%
“…Very recently, shaping has also been used in the particular context of designing multi-processor System-on-Chip (SoC) architectures. It has been shown that shaping on-chip traffic leads to reduced on-chip global buffer requirements and improves overall system performance and predictability [8,14]. Similar techniques have also been shown to be useful when applied to Networks-on-Chip (NoC) architectures, where again they result in improved worstcase response times and global buffer requirements (which in turn lead to reduced chip area and power consumption) [10].…”
Section: Relation To Previous Workmentioning
confidence: 95%
“…Very recently, shaping has also been used in the particular context of designing multiprocessor system-on-chip (SoC) architectures. It has been shown that shaping on-chip traffic leads to reduced on-chip global buffer requirements and improves overall system performance and predictability [Heithecker and Ernst 2005;Wandeler et al 2006]. Similar techniques have also been shown to be useful when applied to networks-on-chip (NoC) architectures, where again they result in improved worst-case response times and global buffer requirements (which, in turn, lead to reduced chip area and power consumption) [Manolache et al 2006].…”
Section: Relation To Previous Workmentioning
confidence: 98%
“…Recently, shaping techniques have also attracted a lot of interest within the embedded systems domain [Cai and Lu 2005;Chiasserini and Rao 2001;Heithecker and Ernst 2005;Hu and Lu 2005;Poellabauer and Schwan 2004;Manolache et al 2006;Wandeler et al 2006]. Shaping has been used as a means for aggregating the workload of media-processing applications (e.g., video decoders) to create idle periods.…”
Section: Relation To Previous Workmentioning
confidence: 99%
“…The memory scheduler is often very dynamic and uses information about the memory state when scheduling to improve average bandwidth or reduce average latency. Optimizing bandwidth may involve preferring requests that target an open row in a bank [52], [46], [53], requests that fit with the current direction of the data path [54], [55], [56], or a combination of the two [57], [58], [59]. Example mechanisms that reduce average latencies is to prefer reads over writes [53], which is beneficial if reads are blocking while writes are posted, or let high-priority memory clients preempt lower priority clients [59].…”
Section: E Memory Controllermentioning
confidence: 99%